2015
DOI: 10.1039/c5tb00075k
|View full text |Cite
|
Sign up to set email alerts
|

Self-healable, super tough graphene oxide–poly(acrylic acid) nanocomposite hydrogels facilitated by dual cross-linking effects through dynamic ionic interactions

Abstract: Here we propose a facile, one-pot in situ free radical polymerization strategy to prepare self-healable, super tough graphene oxide (GO)/poly(acrylic acid) (PAA) nanocomposite hydrogels by using Fe 3+ ions as a cross-linker. The 3-dimensional network structure of the GO/PAA nanocomposite hydrogels is facilitated by dual cross-linking effects through dynamic ionic interactions: (i) first cross-linking points 10 are Fe 3+ ions creating ionic cross-linking among PAA chains; (ii) second cross-linking points are GO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
153
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 264 publications
(157 citation statements)
references
References 56 publications
4
153
0
Order By: Relevance
“…Basically, cross-linkings may be divided into two different types, i.e., chemical (covalent bonds) and physical (ionic bonds, hydrogen bonds, etc.). In the past decades, hydrogels have received increasing attention owing to a wide range of potential applications, including tissue engineering, drug delivery, membrane separation, electrolytes and soft robot [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However, most of the existing natural and synthetic hydrogels have poor mechanical properties, which unfortunately limit their applications in many fields where tough and flexible hydrogels are necessary.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Basically, cross-linkings may be divided into two different types, i.e., chemical (covalent bonds) and physical (ionic bonds, hydrogen bonds, etc.). In the past decades, hydrogels have received increasing attention owing to a wide range of potential applications, including tissue engineering, drug delivery, membrane separation, electrolytes and soft robot [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However, most of the existing natural and synthetic hydrogels have poor mechanical properties, which unfortunately limit their applications in many fields where tough and flexible hydrogels are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the existing natural and synthetic hydrogels have poor mechanical properties, which unfortunately limit their applications in many fields where tough and flexible hydrogels are necessary. In this sense, a surge of research has been reported on the development of nanocomposite hydrogels reinforced with various nanofillers, including clay nanosheets [16], silica nanoparticles [6,9,17], graphene oxide (GO) nanosheets [7,[18][19][20][21][22] and carbon nanotubes [23]. Recently, we have prepared a high-strength GO/PAA nanocomposite hydrogels composed of a single network with dual crosslinking points through dynamic ionic interactions [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, selfhealing materials [6][7][8][9][10][11][12] are under rapid development to improve the lifetime, safety, energy efficiency and environmental impact of synthetic materials. The past few decades have witnessed a rapid development in exerting such features into articial systems where polymers are used for self-healing applications.…”
Section: Introductionmentioning
confidence: 99%